What Are the Determinants of a Workplace Health Promotion? Application of a Social Marketing Model in Identifying Determinants of Physical Activity in the Workplace (a Qualitative Study) - Mohammad Hossein Kaveh; Mehdi Layeghiasl; Mahin Nazari; Leila Ghahremani; Masoud Karimi (Frontiers Media S.A., 2021)
Background and objective: Physical activity is an important behavior to reduce the risk of non-communicable diseases. Providing the context for physical activity in the workplace in addition to promoting the employees' physical and mental health has significant economic benefits for organizations. We conducted the present study using a social marketing model to explain the determinants of a Workplace Health Promotion in promoting physical activity among employees of government organizations in Yasuj, Iran.Materials and methods: The present study was qualitative research with directed content analysis based on the social marketing model. Thirty-three employees of government organizations in Yasuj were included in the study using the purposive sampling method. The data collection method included semi-structured interviews and observation. Data analysis was performed manually and by the qualitative content analysis method. The implementation data were systematically sorted and analyzed and classified into five steps.Results: Organizational structure, organizational policies, and a supportive interpersonal climate were extracted and categorized as characteristics of workplace health promotion programs from participant interviews. In addition to participants' emphasis on receiving information from reputable sources, virtual communication networks such as WhatsApp and real communication networks such as physicians and specialists were their preferred media for education and information.Conclusion: Due to the complexity of workplace, diversity, and multiplicity of factors and determinants of physical activity, the findings of the present study will be a basis for designing an appropriate and effective intervention and organizational changes to promote physical activities among employees in the future.